2016
DOI: 10.18632/oncotarget.13548
|View full text |Cite
|
Sign up to set email alerts
|

RhoA regulates resistance to irinotecan by regulating membrane transporter and apoptosis signaling in colorectal cancer

Abstract: Colorectal cancer (CRC) is a major cause of mortality and morbidity worldwide. While surgery remains the mainstay of treatment in early stage CRC, chemotherapy is usually given to prolong the overall survival and improve the quality of life for metastatic colorectal cancer (mCRC). But drug resistance is one of the major hurdles of mCRC treatment, and the underlying mechanisms are still largely unknown. In this study, we show that, compared with parental cells, RhoA is up-regulated in irinotecan (CPT-11)-resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…S4B-S4E). RhoA has been previously shown to regulate MDR1-mediated resistance to irinotecan and doxorubicin in colon cancer cells (43,44). Our findings suggest that GPR56 regulation of drug resistance is RhoA-mediated, yet the cognate ligand and signaling mechanism downstream of RhoA is unclear.…”
Section: Discussionmentioning
confidence: 71%
“…S4B-S4E). RhoA has been previously shown to regulate MDR1-mediated resistance to irinotecan and doxorubicin in colon cancer cells (43,44). Our findings suggest that GPR56 regulation of drug resistance is RhoA-mediated, yet the cognate ligand and signaling mechanism downstream of RhoA is unclear.…”
Section: Discussionmentioning
confidence: 71%
“…11 GPR56 promotes drug resistance of colorectal tumor by up-regulating MDR1 expression via a RhoA-mediated mechanism. 31 MRP1 is multidrug resistance-associated protein, and BCRP is breast cancer resistance protein. Therefore, we presumed that ANLN knockdown may inhibit the expression of MDR1 and BCRP by repressing RhoA.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the gene profiles of 137 colorectal tumor samples in humans, it was indicated that RHOA is one of the most altered gene among RAS homologues, and RHOA expression shows a positive correlation with survival time [ 87 ]. Beside this, RHOA was found to be upregulated in chemoresistant-CRC, playing a role in the expression of cell membrane transporter and apoptosis in colon cancer, contributing to chemotherapeutic resistance in colorectal cancer patients [ 88 ].…”
Section: Rhoa (Ras Homology Family Member A)mentioning
confidence: 99%